How managerial ownership and the market for corporate control can improve investment timing - Guthrie, Graeme; Hobbs, Cameron (Journal of Banking & Finance, 2021)
We show how CEO ownership and the market for corporate control interact to influence the investment-timing decisions of empire-building CEOs. The prospect of a future takeover means that CEOs with no ownership stake will over-invest in some types of projects and under-invest in others, but these problems are less severe when CEOs have an ownership stake. The value-maximizing level of CEO ownership depends on a firm’s investment opportunities. Antitakeover laws that weaken a raider’s position in a hostile takeover induce raiders to launch friendly takeovers sooner. The increased takeover threat induces CEOs to delay investing in positive NPV projects, but encourages them to take actions that initiate selling the firm when the takeover gains are high. Optimal ownership-generated incentives and the market for corporate control add more value after antitakeover laws are introduced, especially in situations when potential takeover gains are large.